Engineered Minichromosomes in Plants - Prof. Prafulla Kumar Das, Mr. Asit Prasad Das, Rajesh Kumar Ka (International Journal of Modern Agriculture, 2020)
In several plant species, modified minichromosomes were produced by chromosomal truncation telomere-mediated. This approach overcomes the complexities of the epigenetic nature of the centromere role in plants, which has stopped minichromosomes being generates in a plant cell by reintroducing centromere sequences. Gens are linked together with telomere repeats on the one side for cleaved chromosome attachment. When these constructs are implanted in plant cells, the genes are attached to the damaged chromosomes, but the repeats of telomere at the other end, at that stage, can catalyze the creation of a telomere. The chromosome truncation induced by telomers is sufficiently effective to generate very small chromosomes composed essentially of endogenous centromers and the transgenes attached. The transgenes introduced provide a framework for constructing a synthetic chromosome according to specification. The combination of evolved minichromosomes and double haploid replication will substantially speed up transfer of transgenes to new lines and the association of transgenes with genotypes in new background the discussion will focus on potential basic and applicable applications of synthetic chromosomes.